Late Antique and Early Byzantine Era Inscriptions at Assos - Özhan, Tolga (Tekmeria, 2018)
In this paper, eleven new inscriptions are presented, which were found between 1981 and 2017 at Assos in the southern Troad, Asia Minor. Funerary inscriptions that can be dated to the Late Antique and Byzantine periods constitute the majority of the inscriptions found during the period defined above. The first inscription, carved on a lintel, is an acclamation of the Lord/ Emmanouel. The personal name Chrysogonos in the second inscription may have been the name of a stonecutter who worked in the quarry. The third inscription is the epitaph of the gravediggers of the Orthodox “Great Church”. By the phrase “Great Church” (μεγάλη ἐκκλησία), a cathedral must have been intended, located inside the city or its immediate surroundings. The fourth inscription presented here is the sarcophagus inscription of the heirs of an individual called Daniel. The fifthis the sarcophagus inscription of Theoktistos. The inscriptions nos. 6-10 from the oor of Ayazma Church include several sarcophagus inscriptions: No. 6 is of Bas(s)os, no. 7 is of Eutychianos, and no. 8 is of Onesimos, whose father’s name is uncertain due to a crack and damage on the surface of the stone. No. 9 is the sarcophagus of presbyter Anastasios, and no. 10 is the sarcophagus of Eugenios. The eleventh inscription is a fragmentary sarcophagus inscription.